BAB AL - QAWAID : KESULTANAN SIAK DIBAWAH PEMERINTAHAN SULTAN SULTAN SYARIF HASYIM ABDUL JALIL SYARIFUDDIN 1889-1908 - Fahrian, Ion; Melay, Ridwan; Saiman, Marwoto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Indonesia is one of the nation with a diverse culture. Talking about the cultural history of Indonesia itself has developmental stages of Indonesian culture in each period. Region Indonesia has many islands which is united by the sea so that Indonesia has a history of cultural development are not uniform. Speaking of Indonesia alone is inseparable with the history of the kingdoms that once stood in the area of Indonesia. Kingdoms in Indonesia had growth and development into forms of great unity . Development and growth is closely linked to the existence of kingdoms in Indonesia such as Hinduism, Buddhism and Islam . The existence of these kingdoms has colored the history of the kingdom in Indonesia. Kingdoms in Indonesia is very much influence on Indonesian society in general.Data analysis using historical writing. The historical method is the process of test and analyze the testimony of history to find datau authentic and trustworthy, as well as efforts on the synthesis of such data be reliable historical story. Thus the use of historical method is to collect material patterned history , then critically assessed so as to produce a form of scientific writing . This is in line with the objective historical method which makes reconstruction of the past systematically and objectively by collecting , assessing and evaluating and explaining synthesizing evidence to establish facts and reach conclusions that can be maintained . In this case the historical method has four stages, namely : 1). Heuristics 2). Verification 3). Interpretation 4). HistoriographyKeywords: BAB AL - qawaid , Siak , Government , Sultan Syarif Hasyim Abdul Jalil Syarifuddin